The Effects of Carbaryl on the Development of Zebrafish (Danio rerio) Embryos - Schock, Elizabeth N. (Mary Ann Liebert, Inc., 2012)
In the United States, Sevin(™) brand insecticide is one of the most commonly used insecticides. The active ingredient in Sevin(™), carbaryl (1-napthyl-N-methylcarbamate), is a known acetylcholinesterase (AChE) inhibitor that prevents the breakdown of acetylcholine to acetate and choline at the synapse. While carbaryl successfully causes the death of insects by paralysis, it has also been shown to have negative effects on the development of several nontarget species. To study the effects of carbaryl on nontarget species, zebrafish (Danio rerio) were used, as they are a good model for both toxicology and development studies. Our study suggests that carbaryl induces changes in morphology, specifically in embryo size and shape. Additionally, carbaryl causes defects in heart formation that is characterized by a decrease in heart rate and a developmental delay/defect in cardiac looping. A significant decrease in the number of spinal cord neurons present was also observed. Further investigation showed that there was an increase in cell death in carbaryl-treated embryos. The results indicate that carbaryl may have a greater environmental impact than initially intended. Our study, which was conducted solely by undergraduates at a liberal arts college, indicates that carbaryl may be detrimental to the development of nontarget species.